Discriminación, sexo y religión del personal docente - Maldonado Montoya, Juan Pablo (Vergentis, 2025)
In addressing the issue of discrimination based on sex and religion in the educational field, we have decided to limit our discussion to two areas: private educational institutions with a specific ideology, and the group of religion teachers in public educational institutions. These are the two areas where, in light of case law, the three terms: religion, gender, and discrimination, most easily converge. We will attempt to do so by analyzing the most relevant rulings of Spanish courts. Any other approach would lead to either excessive case studies or abstraction, which would require a much more extensive work.